Political Branding : Content Analysis Of Debate Of Candidates For Vice Governor Of East Java Session I In Poverty Reduction - Pratama, Bayu Indra; Ilahi, Azizun Kurnia; Amalia Avina, Diyah Ayu (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to understand how the Political branding strategy developed by the Candidates for Governor and Vice governor with regard to poverty alleviation in the East Java region. This